Improving “No‐Reflow” After Complete Reperfusion: The Role of Intravenous Thrombolysis in Vertebrobasilar Artery Occlusion Patients Undergoing Endovascular Treatment - Zhanglin Li; Yingjie Xu; Pan Zhang; Miaomiao Hu; Ruyue Wang; Zhixin Huang; Zuowei Duan; Xinfeng Liu; Wen Sun (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Previous studies have found that the use of intravenous thrombolysis (IVT) before endovascular treatment (EVT) could mitigate the “no‐reflow” phenomenon in large‐vessel occlusion of the anterior circulation. However, the effect of preoperative IVT on reducing the “no‐reflow” phenomenon in vertebrobasilar artery occlusion (VBAO) is still uncertain. This study aimed to compare the outcomes of IVT before EVT versus EVT alone in patients with VBAO with complete reperfusion (mTICI [Modified Thrombolysis in Cerebral Infarction] 3). Methods We performed a retrospective analysis of patients with acute VBAO at 65 stroke centers in China. Patients with complete reperfusion after EVT were included. These patients were divided into 2 groups on the basis of whether IVT was used before EVT, and propensity score matching was applied to balance the groups. The primary outcome was favorable functional outcome, defined as a modified Rankin Scale score of 0 to 3 at 90 days. Secondary outcomes were functional independence (modified Rankin Scale score of 0–2 at 90 days) and modified Rankin Scale shift at 90 days. Safety end points included symptomatic intracranial hemorrhage and death at 90 days. Results Of the 2422 patients with VBAO who received EVT, 1452 patients achieved complete reperfusion. Among these, 273 patients received IVT before EVT. After propensity score matching, 268 patients treated with IVT before EVT were compared with 519 patients without IVT. In the matched cohort, the group that received IVT before EVT showed a higher rate of favorable functional outcome (modified Rankin Scale score, 0–3) (adjusted odds ratio, 1.40 [95% CI, 1.03–1.91]; P=0.033) and a lower mortality rate at 90 days (adjusted odds ratio, 0.72 [95% CI, 0.52–0.99]; P=0.044) compared with the EVT alone group. Conclusions Our study indicates that IVT before EVT could improve favorable functional outcomes and reduce death in patients with VBAO who achieve complete reperfusion.